Avaliação de problemas relacionados a medicamentos e qualidade de vida em pacientes chagásicos usuários de benzonidazol - Sousa Junior, Alcidésio Sales de (2008)
Drug Related Problems (DRP) are responsible to cause morbidity and mortality in all world, and can affect expected clinical results and quality of life (QoL) of patient. Etiologic treatment for Chagas’ disease (caused by Trypanosoma cruzi) have only a drug, the benznidazole (BNZ). This medicine may produce toxicity (hipersensibility, bone medular aplasy, etc.) and have partial efficacy. The aim was to estimate the effects in the health of patients in use of BNZ, mensured by QoL and DRP. Nineteen patients included in a observational, descriptive and follow-up study in the period from November of 2006 to October of 2007. These patients, after prescription of BNZ and consent, were followed by 6 months by pharmacist and pharmacist students. Dader Method was utilized except intervention procediment. DRP were classified by judges utilizing the Second Granada Consensus (2002). The adverse reaction were classified by Centro de Farmacovigilância do Ceará (CEFACE). The QoL was mensuread by Short-Form Health Survey (SF-36) questionnaire before and after the follow-up. Were realized by descriptive analysis to study the result. Also, Mcnemar and Wilcoxon tests were made for inferential analysis, considering the significance level p<0,05. The majority of patients were men (58%), had until primary school level (57,9%) and they were in a indeterminate form of Chagas disease (74). About 42 from patients used 2 or 3 medicines with BNZ treatment, with an average from 1,3 medicine per patient. Antihypertension and diuretics were the most utilized in BNZ treatment (22%). In relation to adherence, 47,4% from patients were not adhere to BNZ. The use of BNZ was suspended in 36,8% of patients, the major reason was adverse reaction (Correlation Coefficient = 0,415, p-value = 0,047). In three steps of analysis was founded a total of 148 DRP (41,9% related to necessity, 33,1% to effectiveness and 25% to security). DRP were associated to number of medicines (Kendall Coefficient = 0,438, p-value = 0,018). The number of DRP were high after than the start of treatment with BNZ (Wilcoxon test: Z=-3,725, p<0,05). Seventeen patients (10 men and 7 women) showed adverse reaction, to pruritus until parestesia. These majority reactions were classified as probable and soft. Patients with soft adverse reaction have more knowledge level in relation to patients with moderate adverse reaction (Correlation Coefficient = 0,523; p-value = 0,028). It wasn’t detected alterations in QoL after follow-up, but it was showed that DRP affected QoL levels (Wilcoxon test: Z=-3,724, p<0,05). There wasn’t difference between QoL before and after, however DRP affected QoL.